PRMT5 controls the innate immune response - Zhang, C (2024)
Protein arginine methyltransferase 5 (PRMT5) is a symmetric di-methyltransferase frequently overexpressed in various cancers, including colorectal cancer. It is known that PRMT5-mediated methylation of E2 promoter binding factor 1 (E2F1) not only supports cancer cell growth but also influences RNA splicing. Previous studies have shown that inhibition of PRMT5 suppresses tumour growth and induces apoptosis in colorectal cancer cells. However, the underlying mechanisms remain insufficiently understood. This study explores a novel pathway involving an innate immune response triggered by PRMT5 and E2F1-mediated RNA splicing. We hypothesised that PRMT5 inhibition could increase retained introns (RIs) in the colorectal cancer cell line HCT116, leading to the production of immunogenic double-stranded RNAs (dsRNAs). Using the PRMT5 inhibitor T1-44, we observed increased intron retention and subsequent accumulation of dsRNAs and interferon-beta (IFN-β) both in vivo and in vitro, in an E2F1 dependent manner. Previous replicate multivariate analysis of transcript splicing (rMATS) analysis identified a pool of genes undergoing increased intron retention with T1-44 treatment.